Analysis of Kaizen Culture on Ship Loading and Unloading Performance at PT. Tanto Intim Line Pelayaran Nusantara - Retno Sawitri Wulandari; Suhartini; Meilinasari Nurhasanah Hutagaol (Meteor STIP Marunda, 2023)
The low performance of PT. Tanto Intim Line Pelayaran Nusantara employees is reflected in the quantity and quality of their work, which do not meet the company’s targets. Organizational culture, particularly the Kaizen philosophy rooted in continuous improvement, has been widely recognized as a critical determinant of employee productivity and operational efficiency in the maritime logistics sector. Therefore, the research team aims to use this study to analyze the organizational culture—specifically, a culture focused on Kaizen (5S: Seiri, Seiton, Seiso, Seiketsu, Shitsuke)—and its impact on the performance of ship cargo handling at the shipping company PT. Tanto Intim Line Pelayaran Nusantara. The research method employed by the team is a quantitative descriptive method utilizing simple linear regression analysis. The population and sample size consist of 30 respondents from the ship loading and unloading division, and the sampling technique used is saturation sampling (census). Data were collected through closed-ended questionnaires and company documentation. Instrument validity was verified using Pearson product-moment correlation (r-table = 0.361, α = 0.05), and reliability was confirmed through Cronbach’s alpha (α > 0.60). The results of the research indicate that the Kaizen culture has a positive and significant influence on the performance of ship cargo handling, as evidenced by a correlation coefficient (R) of 0.751, a coefficient of determination (R²) of 56.5%, and a t-test value of 6.026 > t-table 2.048 (sig. 0.000 < 0.05). These findings confirm that implementing Kaizen culture contributes substantially to improving operational performance in maritime cargo handling operations.